PENERAPAN PELAKSANAAN AKUNTANSI PERTANGGUNGJAWABAN DALAM PENILAIAN KINERJA - Anisa Widiastuti; Syahla Salsabila; Agus Munandar (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2022)
Performance is something that functions to achieve the success of a company. Performance is a part that must be confirmed to find out the achievements of a company. Basic system used in this performance is responsibility accounting. Responsibility accounting is one of the most important components of all control in a company. Responsibility accounting is used as a process of collecting and presenting a financial report. One of the systems in responsibility accounting that contains how to control costs for production and non-production. From the results of this study showing to find out how the implementation of accountability accounting in performance research at CV Kenari Furniture, Majasari Distric, Pandeglang, Banten. In this study, the method used is descriptive qualitative. Based on accountability accounting information data, this method describes empirical and factual data based of CV Kenari Furniture. Qualitative descriptive method which contains analytical analysys so that it can obtain conclusions based on objectives. From the results of this study, it was stated that at CV Kenari Furniture the planning and implementation of accountability accounting had been implemented and was quite good. In the application of CV Kenari Furniture's responsibility accounting, namely by providing work safety insurance and severance pay. Keywords : Responsibility Accounting, Employee Performance Appraisa